Iron Metabolism, Ferroptosis, and the Links With Alzheimer’s Disease - Yan, Nao; Zhang, JunJian (Frontiers in Neuroscience, 2020)
Iron is an essential transition metal for numerous biologic processes in mammals. Iron metabolism and homeostasis are regulated via several coordination mechanisms including absorption, utilization, recycling, and storage.Iron dyshomeostasis can result in intracellular excessive iron accumulation,thereby damaging cells, tissues and organs through free oxygen radicals generation. Numerous studies have showed that iron overload of brain is involved in the pathological mechanism of Alzheimer’s disease.However,the underlying mechanisms have not been fully elucidated. Ferroptosis , a newly defined iron-dependent form of cell death, which is distinct from apoptosis, necrosis, autophagy and other forms of cell death,may provide us new viewpoints. Here, we summarizes the current knowledge of iron metabolism and ferroptosis, and reviews the contributions of iron and ferroptosis in Alzheimer’s disease.